The lost vent gastropod species of Lothar A. Beck - Chen, Chong; Sigwart, Julia D. (Zootaxa, 2023)
Deep-sea hydrothermal vents host many endemic species adapted to these chemosynthesis-based ecosystems. The exploration of vent fields including those in the tropical Pacific is currently accelerating, due to the development of deep-sea mining for valuable minerals. Molecular evidence has shown that many vent endemic gastropod lineages include sibling species pairs in adjacent oceanic basins. While the fauna of the Manus Basin is relatively well described, many lineages in adjacent regions in North Fiji or Lau Basins are recognised as separate species, but unnamed. Valuable material from this fauna was studied by Lothar A. Beck in the 1990s, who fully drafted descriptions for these species, but did not publish them. Beck’s manuscript names, prior to the present study, represented real species but nomina nuda without taxonomic validity. Here we present the descriptions of seven new species and one new genus, extracted from Beck’s unpublished manuscript that was rediscovered after his death in 2020. The publication of these descriptions makes them taxonomically available and respects the scientific contributions of Beck. Providing valid descriptions of these species is critically important now to enable the recognition of species that may require conservation in the face of future environmental destruction.Symmetriapelta Beck, gen. nov. is described as new genus. Bathyacmaea nadinae Beck, sp. nov., Pyropelta ovalis Beck, sp. nov., Pseudorimula leisei Beck, sp. nov., Lepetodrilus fijiensis Beck, sp. nov., Shinkailepas conspira Beck, sp. nov., Symmetromphalus mcleani Beck, sp. nov. and Symmetriapelta wareni Beck, sp. nov. are introduced as new species.